If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) + -12x = 48 Reorder the terms: 3(4 + x) + -12x = 48 (4 * 3 + x * 3) + -12x = 48 (12 + 3x) + -12x = 48 Combine like terms: 3x + -12x = -9x 12 + -9x = 48 Solving 12 + -9x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -9x = 48 + -12 Combine like terms: 12 + -12 = 0 0 + -9x = 48 + -12 -9x = 48 + -12 Combine like terms: 48 + -12 = 36 -9x = 36 Divide each side by '-9'. x = -4 Simplifying x = -4
| lnx=70.0173683 | | 2q+5y+4z=0 | | 8h-24=36 | | 12x-11=15x-10 | | 12=(n-1)(n-2)(n-3)(n-4)(n-5)-3n^2 | | -36=y-5y-21 | | 12=(n-1)(n-2)(n-3)(n-4)-(2n^3) | | 12=n^4-12n^3+35n^2-50n+24 | | 8+4x=7x | | -11-5X=-111 | | (y+3)2=25 | | 8x=20x^2 | | 18x-5y=90 | | -6+w+w=9+w | | 2y-y-9y= | | y=1E+06x+2E+06 | | 3x+2x+x-3=27 | | 3+8y=3(2x)-1 | | 12-2y=8(y+4) | | 12-2y=8(x+4) | | X(X-8)=1280 | | 5x+16=3x+42 | | 5(2x-7)=3x | | 8e-8=64 | | x+3+2x=63 | | 7(a+4)=77 | | 2x+3=8x-39 | | -13x+8=-96 | | 2b+7a+4=(b+a)(b-a) | | 2b+7a+4=(b+a)*(b+a) | | b^2+a^2=2b+7a+4 | | x^3=5x^2-5 |